Alterations in Synovial Fluid Biomarker Levels in Knees With Meniscal Injury as Compared With Asymptomatic Contralateral Knees. Issue 4 (March 2019) - Clair, Andrew J.; Kingery, Matthew T.; Anil, Utkarsh; Kenny, Lena; Kirsch, Thorsten; Strauss, Eric J.
Background: Changes in the joint microenvironment after an injury to the articular surface of the knee have been implicated in the pathogenesis of osteoarthritis. While prior studies focused on changes in this microenvironment after anterior cruciate ligament ruptures, few have explored the biomarker changes that occur in the setting of meniscal injuries. Purpose: To determine whether meniscal injury results in significant alterations to synovial fluid biomarker concentrations as compared with noninjured contralateral knees. Additionally, to explore the relationship between synovial fluid biomarkers and the degree of cartilage injury seen in these patients. Study Design: Cross-sectional study; Level of evidence, 3. Methods: Patients undergoing surgery for unilateral meniscal injury were prospectively enrolled from October 2011 to December 2016, forming a cohort that had synovial fluid samples collected from both the injured knee and the contralateral uninjured knee at the time of meniscal surgery. Synovial fluid samples were collected just before incision, and the concentrations of 10 biomarkers of interest were determined with a multiplex magnetic bead immunoassay. The concentrations of synovial fluid biomarkers from the operative and contralateral knees were compared. Additionally, the synovial fluid biomarker concentrations of operative knees from patients with associated high-grade cartilage lesions were compared with those with low-grade lesions. Results: The current analysis included synovial fluid samples from 82 knees (41 operative and 41 contralateral) from 41 patients undergoing arthroscopic surgery to treat a symptomatic meniscal injury. The mean ± SD age of patients was 49.86 ± 11.75 years. There were significantly greater concentrations of 4 of the 5 proinflammatory biomarkers (IL-6, MCP-1, MIP-1β, and MMP-3) in symptomatic knees as compared with asymptomatic knees when controlling for the duration of symptoms, body mass index, age, and the random effects of by-patient variability. In the injured knees, associated high-grade cartilage lesions were predictive of elevated MCP-1, MIP-1β, and VEGF levels. Low synovial fluid concentration of TIMP-1 or a greater ratio of MMP-3 to TIMP-1 was associated with the presence of synovitis. Increasing age was found to be an independent predictor of increased IL-6, MCP-1, and VEGF concentrations in the setting of symptomatic meniscal injury. Conclusion: The authors identified 4 proinflammatory synovial fluid biomarkers whose concentrations were significantly different after meniscal injury as compared with uninjured contralateral knees. Furthermore, they describe the effects of associated cartilage damage, synovitis, and patient age on biomarker concentrations.